2007
DOI: 10.2208/jsceseee.24.62s
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Based Damage Detection in Flexible Risers Using Time Series Analysis

Abstract: In this paper, a statistical pattern recognition method based on time series analysis is implemented in flexible risers. This method uses a combination of Auto-Regressive (AR) and Auto-Regressive with eXogenous inputs (ARX) prediction models. The flexible riser model used in this paper is experimentally validated employing a proposed numerical scheme for dynamic response of flexible risers. A modal-based damage detection approach is also implemented in the flexible riser model and its results are compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is also a frequency domain method based on output data, which is not applicable to deepwater risers with varying natural frequencies. Riveros et al 10 suggested that a statistical pattern recognition method with a combined model with auto-regressive (AR) and auto-regressive with exogenous inputs (ARX) works better than modal distribution method. However, in deepwater situation, the inputs are unknown, which means the method is not suitable.…”
Section: Current Riser Monitoring and Inspection Methodsmentioning
confidence: 99%
“…This is also a frequency domain method based on output data, which is not applicable to deepwater risers with varying natural frequencies. Riveros et al 10 suggested that a statistical pattern recognition method with a combined model with auto-regressive (AR) and auto-regressive with exogenous inputs (ARX) works better than modal distribution method. However, in deepwater situation, the inputs are unknown, which means the method is not suitable.…”
Section: Current Riser Monitoring and Inspection Methodsmentioning
confidence: 99%